PREVENTIVE MECHANISM AGAINST SIMPLE AND COOPERATIVE BLACK HOLE ATTACKS IN MULTI-HOP WIRELESS AD HOC NETWORKS - R, Praveenkumar; S, SivaSankaran (IJRDO -Journal of Computer Science Engineering, 2015)
This paper focuses on the issues related to the simple and cooperative black hole attacks in multihopwireless ad hoc networks. In multi-hop wireless ad hoc networks, nodes not in direct rangerely on intermediate nodes to communicate. In order to preserve its limited resources or to launcha DoS attack, an intermediate node drops packets going through it instead to forward them to itssucces- sor. In this paper, we deal with this misbehavior called black hole attack, and we proposean authenticated end-to-end acknowledgment based approach in order to check the correctforwarding of packets by intermediate nodes. Our approach detects the black hole conducted insimple or cooperative manner, the modification and the replay of messages attacks. Throughsimulation using OPNET simulator, we show the detection efficiency and evaluate theperformance of our approach in both proactive and reactive routing based networks in terms ofend-to-end delay and network load. Also, we compare the approach we propose with 2-hop ACKand the watchdog approaches in terms of detection ratio, delivery ratio and additional overhead.